Efektifitas Hiddent Curriculum dalam Pengembangan Karakter Religius Santri - Ainul Yakin; Khoirul Amin (STAI Syaichona Moh. Cholil Bangkalan, 2021)
This research objective was to determine effectiveness, the impact and supporting factors as well as hidden curriculum obstacles to the development of the religious character of students at the Nurul huda Islamic boarding school in Pakandangan Barat Bluto Sumenep in 2020. This research uses a qualitative approach with a type of case study, the research data collection instrument was an interview, observation and documentation. The data source is divided into two parts, namely : primary data, in the form of data obtained and collected directly themselves. Meanwhile, secondary data is in the form of literature, article, journals and some web. Data analysis techniques with data coordinating steps, find a pattern shape, get the important things and save data. The results show that the Hidden Curriculum can have an effect on the development of the religious character of the santri at the Nurul huda Pakandangan Barat Islamic boarding school, Bluto Sumenep. Among them : 1) Can Stabilize the memorization of alqura'n students, 2) Can get students used to saying greetings, 3) Able to get students used to throwing garbage in its place, 4) can develop knowledge and make it easier for students to find classical books, and 5) Can get students used to reading prayers when marosim (control before activities). The impact of the Hiddent Curriculum consists of positive and negative impacts. Positive impacts, namely 1) There is an increase and balance of soft skills and hard skills, and 2) Increase the discipline of students. While the negative impacts are: 1) Not through in-depth research, and 2) Requires intensive monitoring. While the supporting factors are, 1) The presence of students and teachers for 24 hours in the cottage and 2) a conducive social environment, Meanwhile, the inhibiting factors are 1) Some parties do not know the meaning of the Hiddent Curriculum and 2) The lack of facilities and costs.